EVALUASI AKTIVITAS PUBLIC RELATIONS PT. COCA-COLA AMATIL INDONESIA CABANG DENPASAR (STUDI PADA: COCA-COLA PLANT TOUR TAHUN 2016) - Anggrisari Animoy Borromeu, Gardenia Mega; Purnawan, Ni Luh Ramaswati; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2018)
ABSTRACT In the work process of public relations, there are several stages of work management process. One of them is the evaluation stage, where in this stage public relations would evaluate the results of the work program that have been implemented. Through the special event “Coca-Cola Plant Tour “ that is conducted by public relations of PT. Coca-Cola Amatil Indonesia, the company expects that the purpose of the work program could be achieved well. The SWOT analysis theory is used to do the research in the work program evaluation called “Coca – cola Plant Tour”. The purpose of this study is to know the activities evaluation of Public Relations PT. Coca-Cola Amatil Indonesia in Denpasar Branch especially at Coca-Cola Plant Tour Bali 2016. The descriptive qualitative method is used in this study. The results of this study indicate that the role of Public Relations run by the Public Affairs and Communications Division at PT. Coca-Cola Amatil Indonesia in Denpasar branch is as Communication Facilitator and Communication Technician. It could be seen in doing some activities as a responsible in it and in the information management that is available at several points in Coca-Cola office, therefore, it is easy to reach by all office employees (canteen, working room and each floors). Based on SWOT analysis, researcher found some strengths, weaknesses, threats and opportunities for PT. Coca-Cola Amatil Indonesia especially at Coca-Cola Plant Tour activities. The Strength and the opportunity are the PT. Coca-Cola Amatil Indonesia is an international company which is spread everywhere and these activities could provide the understanding in purpose to maintain the good image of the company. The weaknesses and the threat are a bad image of carbonated drink and the existence of similar activities programs that is held by a competitor company. Keywords : Coca-Cola, Coca-Cola Plant Tour, Evaluation, SWOT Analysis